2019
DOI: 10.1101/2019.12.17.879932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A polarized nucleus-cytoskeleton-ECM connection controls collective migration and cardioblasts number inDrosophila

Abstract: The formation of the cardiac tube is a remarkable example of complex morphogenetic process conserved from invertebrates to humans. It involves coordinated collective migration of contralateral rows of cardiac cells. The molecular processes underlying the specification of cardioblasts prior to migration are well established and significant advances have been made in understanding the process of lumen formation. However, the mechanisms of collective cardiac cells migration remain elusive. Here we identified CAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In the middle development, the mechanism of dorsal closure could also be a sophisticated method, involving associate degree orchestration of cell-matrix interaction between smooth muscle cells, epithelial tissue cells, and the ECM [20]. A recent study demonstrated that nucleus-cytoskeleton-ECM connections triggered coordinated cardioblast movements, and controlled cardioblast number in Drosophila [21]. In this review, we will focus on the role of the ECM in the regulation of cardiac development and repair.…”
Section: The Role Of Ecm In Heart Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the middle development, the mechanism of dorsal closure could also be a sophisticated method, involving associate degree orchestration of cell-matrix interaction between smooth muscle cells, epithelial tissue cells, and the ECM [20]. A recent study demonstrated that nucleus-cytoskeleton-ECM connections triggered coordinated cardioblast movements, and controlled cardioblast number in Drosophila [21]. In this review, we will focus on the role of the ECM in the regulation of cardiac development and repair.…”
Section: The Role Of Ecm In Heart Developmentmentioning
confidence: 99%
“…Sci. 2020, 21, 8610 2 of 20 collagens, laminin, elastin, fibulins, proteoglycans, matrix metalloproteinases (MMPs), tenascin-C (TNC), and thrombospodins (TSPs) [18]. In addition, immune cells in the cardiac microenvironment can also produce ECM proteins such as MMPs to modulate the immune response in the heart, contributing to the regulation of cardiomyocyte survival [19].…”
Section: Introductionmentioning
confidence: 99%